Clinical outcomes of kidney transplantation from expanded-criteria donors and KDPI>85% kidneys in deceased Chinese donors - Kankan Shui; Hedong Zhang; Tengfang Li; Jianfei Hou; Gongbin Lan; Fenghua Peng; Shaojie Yu; Xubiao Xie; Helong Dai; Longkai Peng (BMC Nephrology)
Abstract Background Kidney transplantation is the optimal treatment for end-stage renal disease; however, the limited availability of donor kidneys hinders the advancement of this procedure. The utilisation of expanded criteria donor (ECD) kidneys and kidney donor profile index (KDPI) > 85% kidneys represents a significant initiative in addressing this shortage. Our study aimed to investigate the clinical outcomes of kidney transplantation by the ECD and KDPI > 85% kidneys, as well as the risk factors influencing graft survival, with the aim of providing a reference for the clinical application of the ECD and KDPI > 85% kidneys in Chinese population. Methods This retrospective analysis included 326 adult donor kidney transplant recipients from July 2018 to June 2020. The donor kidneys were classified into ECD kidneys (n = 110) and standard criteria donor (SCD) kidneys (n = 216) based on the United Network for Organ Sharing (UNOS) criteria, as well as into kidneys with KDPI > 85% (n = 42) and KDPI ≤ 85% (n = 284), according to the donor’s KDPI value. T tests, chi-square tests, and Mann-Whitney U tests were used to compare complications and renal function following kidney transplantation. Additionally, the log-rank test was used to assess differences in survival rates, whereas Cox regression analysis was conducted to identify risk factors associated with graft loss. Results Analysis revealed that grafts from ECDs exhibited significantly poorer survival rates (P = 0.004), whereas the survival rates of their recipients were comparable (P = 0.710). No significant differences were observed between the ECD and SCD groups regarding the incidence of DGF (22.7% vs. 26.4%, respectively; P = 0.471) or AR (24.5% vs. 25.9%, respectively; P = 0.787). At 3 months, 6 months, 1 year, 2 years, 3 years, and 4 years posttransplantation, the SCr level and eGFR in the ECD group were significantly lower than those in the SCD group (all P < 0.05); however, no differences were noted at 1 month posttransplantation. Furthermore, the SCr level and eGFR in the kidneys of patients with a KDPI > 85% were significantly worse than those in the kidneys of patients with a KDPI ≤ 85% at 6 months, 2 years, 3 years, and 4 years posttransplantation (all P < 0.05), with no differences being observed at 1 month, 3 months, and 1 year posttransplantation. Additionally, no significant differences were observed between the KDPI > 85% and KDPI ≤ 85% groups regarding the incidence of DGF, AR, graft survival, or recipient survival (all P > 0.05). Multivariate Cox regression analysis indicated that ECD kidneys (HR = 3.647, P = 0.003) and AR (HR = 4.675, P < 0.001) were independent risk factors for graft loss. Conclusion In this validation study of the transplant scoring criteria based on the Chinese population, our study indicated that compared with SCD kidneys, ECD kidneys demonstrated poorer graft survival and a tendency towards inferior postoperative renal function. However, the rates of recipient survival, DGF, and AR were comparable. Additionally, graft and recipient survival, as well as the incidence of DGF and AR, in KDPI > 85% kidneys were also similar to those in KDPI ≤ 85% kidneys. Nevertheless, kidneys with a KDPI > 85% tended to exhibit inferior postoperative renal function. Thus, the KDPI score is a valuable tool for predicting graft function in Chinese population.